Labor Epidural Intolerance Due to a Congenitally Narrowed Spinal Canal. Issue 3 (September 2017) - Dickerson, D.M.; Dai, R.; Scavone, B.M.; McDade, W.
Abstract : ( Reg Anesth Pain Med. 2016;41(6):776–779) This case report detailed the complications that arose with epidural analgesia by describing the case of a 34-year-old patient who developed pain in the upper back, neck, and shoulders following bolus injection into the epidural space. These symptoms were due in this patient to congenital spinal stenosis with a significantly narrowed cervical spinal canal.